Defensive Mechanisms and Key Strategies with Its Specified Role in Mulberry Silkworm (Bombyx mori L.) - Karthick Mani Bharathi B; Susikaran S; Allwin Loveson (International Journal of Insects, 2024)
Silkworms (Bombyx mori L.) possess a variety of defense mechanisms that play a vital role in protecting them against microbial infections and environmental stressors. These defense systems are primarily innate, relying on cellular and humoral responses. Cellular defenses include hemocytes which are responsible for processes like phagocytosis, encapsulation, and nodule formation. Humoral responses involve the production of antimicrobial peptides (AMP’s), such as cecropins, moricins, and lysozymes, which target invading pathogens. Heat shock proteins also contribute by stabilizing protein structures during stress conditions like elevated temperatures. Furthermore, silkworms produce reactive oxygen species as part of their immune response thereby helping to neutralize harmful invaders. Recent studies have revealed molecular insights into how these defense mechanisms are activated and regulated. Understanding these immune strategies not only provides insights into insect immunity but also opens potential avenues for enhancing disease resistance in sericulture thereby ensuring better productivity in the silk industry.
Keywords: Antimicrobial protein; Behavioral defense; Cellular immunity; Immune Signaling; Innate immunity